ترويج علم السيرة النبوية في كشمير خلال العهد المغولي: دراسة تحليلية للجهود العلمية للعلامة مير خواجه معين الدين هادي (Khairulummah, 2025)
This study examines the promotion of Sīrah studies in Kashmir during the Mughal period through an analytical investigation of the scholarly contributions of the eminent Naqshbandī scholar, Mīr Khwāja Muʿīn al-Dīn Hādī (d. 1085 AH). The research highlights his role in disseminating the knowledge of the Prophet’s biography (Sīrah) through teaching, spiritual guidance, and literary production. Particular attention is given to his Persian manuscript entitled Khaṣāʾiṣ Aḥmad Muṣṭafā, popularly known as Sair Khwāja Muʿīn Hādī, which represents a significant contribution to Sīrah literature in Mughal India. The study provides a codicological description of the manuscript, preserved in the University of Peshawar Library under manuscript number 344, consisting of 480 pages. It further investigates the circumstances of its composition, the rationale behind its title, and the author’s use of Ḥisāb al-Jummal (Abjad numerical calculation) to align the title with the year of completion, 1075 AH.The research analyzes the structural organization of the work, showing that the author arranged the material into an introduction, fourteen major sections (uṣūl), and a conclusion. The manuscript presents an account of the Prophet’s life, beginning with the Muhammadan Light, followed by his birth, mission, migration, miracles, unique characteristics, family life, and the virtues of his Companions. The author intentionally avoided lengthy narratives concerning previous prophets and unnecessary digressions, thereby maintaining a focused treatment of the Prophet’s biography. From a critical perspective, the study evaluates the author’s methodology in handling historical reports and prophetic traditions. It reveals that although the manuscript reflects devotion to the Prophet ﷺ and an effort to popularize Sīrah studies among Persian-speaking audiences, the author frequently cites traditions without precise references and does not consistently distinguish between authentic and weak narrations. Nevertheless, the work remains an important historical source illustrating the flourishing of Sīrah scholarship in Kashmir during the Mughal era. Overall, the study concludes that Mīr Khwāja Muʿīn al-Dīn Hādī played a significant role in preserving and disseminating the Prophetic biography, and that his manuscript constitutes a valuable contribution to the intellectual and literary heritage of Kashmir.
Keywords: Sīrah al-Nabawiyyah; Kashmir; Mughal Period; Mīr Khwāja Muʿīn al-Dīn Hādī; Naqshbandī Order; Persian Manuscripts; Islamic Scholarship; Prophetic Biography; Indo-Islamic Intellectual History; Sīrah Literature; Mughal India; Kashmir Studies.